2017
DOI: 10.3892/or.2017.5565
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of sulforaphane in regulation of angiogenesis in a co-culture model of endothelial cells and pericytes

Abstract: Abstract. Aberrant neovascularization supports nutrients and the oxygen microenvironment in tumour growth, invasion and metastasis. Recapitulation of functional microvascular structures in vitro could provide a platform for the study of vascular conditions. Sulforaphane (SFN), an isothiocyanate, has been reported to possess chemopreventive properties. In the present study, the effects of SFN on cell proliferation and tubular formation have been investigated using endothelial cells (ECs) and pericytes in cocult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…S2). The concentrations of the SFN, which stimulating angiogenesis in chick YSM and CAM, were higher than the ones used in our in vitro experiments [18][19]32 . This might be due to the diversity and absorptivity between in vivo and in vitro approaches, since the in vivo microenvironment of YSM and CAM are certainly more complicated than one at incubated one layer of cells in .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…S2). The concentrations of the SFN, which stimulating angiogenesis in chick YSM and CAM, were higher than the ones used in our in vitro experiments [18][19]32 . This might be due to the diversity and absorptivity between in vivo and in vitro approaches, since the in vivo microenvironment of YSM and CAM are certainly more complicated than one at incubated one layer of cells in .…”
Section: Discussioncontrasting
confidence: 56%
“…This might be due to the diversity and absorptivity between in vivo and in vitro approaches, since the in vivo microenvironment of YSM and CAM are certainly more complicated than one at incubated one layer of cells in . However, most studies showed more than 10µM SFN could suppress angiogenesis in vitro (HUVECs and Bovine aortic endothelial cells) [18][19][32][33][34][35][36] and in vivo (Balb/C mice implanted with VEGF-impregnated Matrigel plugs) 34 experiments. Our observations are generally similar to the experimental results in those literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this bell-shaped effect of SFN and its analogues on angiogenesis in normoxia has also been found in our previous studies utilizing tumor cells and 3-D HUVECs and pericyte co-culture models. 17,22,24,64 The stimulating action of SFN on angiogenesis has been evidenced in ethanol-injected chick yolk sac membrane (YSM) and chorioallantoic membrane (CAM) models at 2.5–10 μM co-treatment, 65 and in 2.5 μM-pretreated endothelial colony forming cells (ECFCs). 66 In contrast, anti-angiogenic activities of SFN and some other ITCs have also been reported in HUVECs and rat aortic ring models at a single dose (>10 μM) of intervention in normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying the remarkable efficacy are its pleiotropic activities, for example, inducing antioxidant/detoxifying enzymes, anti-inflammation, mitostatic and pro-apoptotic effects, epigenetic regulation of genes, improving metabolism. 6–9 There is also evidence indicating that SFN and its metabolites and analogues possess anti-angiogenic properties, 7,10 and the potential mechanisms, though not fully elucidated, may involve inducing ECs apoptosis, 11,12 inhibiting matrix metalloproteinase-2/9 (MMP-2/9), 13,14 hypoxia-inducible factor-1α (HIF-1α), 13,15,16 vascular endothelial growth factor (VEGF), 13,15,17,18 VEGF receptor-2 (VEGFR-2), 13,18 disrupting endothelial mitotic progression and microtubule polymerization, 19 anti-inflammation, 20 activating FOXO, 21 inhibiting STAT3 22,23 and inducing ROS. 24…”
Section: Introductionmentioning
confidence: 99%
“…study, SFN was found to differentially regulate the EC and pericytes, thereby disturbing their role in the VEGF-VEGFR signaling pathway (Y Wang, Zhou, Wang, Liu, & Bao, 2017)…”
mentioning
confidence: 99%